Mandarin chinese pronunciation crashing : ultimate pinyin training : speak mandarin like a native speaker - LIJIE WANG ([Place of publication not identified] : Jianwu Liu, 2019)
This book is designed for all levels of Mandarin learners whose mother tongue is English to get to know, improve, and eventually master Mandarin pronunciation. Six strategies are introduced in this book to ensure that you reach your goal of learning Mandarin pronunciation:1.Building a bridge between English and Mandarin pronunciations. 2.Offering text and graphic instructions and video demonstrations for every Pinyin sound. 3.Applying enunciation$1 (Bpronouncing Mandarin sounds in a clear and slow manner for learners to follow easily. 4.Providing adequate exercises. 5.Practicing tongue twisters to develop muscle memory to pronounce Mandarin sounds automatically. 6.Linking pronunciation with real-life oral communication.s
Keywords: MANDARIN CHINESE PRONUNCIATION